《“恐怖”的翻译 ：以斯蒂芬 · 金的作品为例来探讨恐怖小说的翻译》= Translating horror : a case study of Stephen King’s works and translating gothic novel - 卢裕盛 Loh, Joo Seng (Nanyang Technological University, 2020)
身为“恐怖小说大师”的斯蒂芬·金在当今美国恐怖小说界可说是无人不知，无人不晓的地位存在。他独特的写作风格可说是以一人之力改变整个小说体裁，重新定义恐怖小说和哥特式小说。善于将各种社会题材以恐怖小说的方式包装起来的他，让读者在吓破胆的同时也在烧破脑。恐怖小说最重要的几个元素包括叙述视角，场景和人物的塑造。只有通过这些细节的总和，才能孕育出一个个让人胆战心惊，让人想落荒而逃的场景。 而翻译是一种跨语言、跨文化、跨社会的交际活动，如何将完整的信息从一个语言搬运到另一个语言并找到相符合的符号是件不容易的过程。因此每一本翻译小说的背后都藏着译者经过多年的累积，经过深思熟虑后的各个翻译策略。如何将“恐怖小说大师”的巧妙安排准确并优美地转换到另一个语言则需要一个好的翻译策略。本文将以斯蒂芬·金的两部小说《嘉莉》和《重生》以及其译作为案例研究，分析译者在翻译恐怖小说时的各种考虑，从而讨论出合适的翻译策略。 Known as “Master of Horror”, Stephen King is a household name in the U.S., well known for his work in horror fiction. His unique style of writing have changed the whole genre through efforts, re-establishing the genre of horror fiction and gothic novels. Great at disguising social themes under the disguise of horror fiction, his novels are one that would make people both scream and think. Important elements of horror fiction includes: the narrative point of view, the establishing of a narrative structure and allowing the development of the character. Only through the combinations of all these elements, it will then be possible to create scary and frightening scenes. Translation is a social activity that cross over different languages, different cultures and different societies, and it is not an easy process to transfer accurately the information from one language to another without any lost in meaning. Hence, behind every translated works lies the years of dedication and efforts by the translator to come up with the appropriate strategy. Translating the works of the “Master of Horror” require a lot of effort and a good translation strategy. Through the investigation of Stephen King’s works “Carrie” and “Revival”, and their respective translated works, this paper will attempt to analyse and decide upon a suitable strategy for translating horror fiction.